The post-activation potentiation effect on sprint performance after combined resistance/sprint training in junior basketball players - Tsimachidis, C.; Patikas, D.; Galazoulas, C.; Bassa, E.; Kotzamanidis, C. (Journal of Sports Sciences, 2013)
The aim of this study was to examine the effect of a 10-week combined resistance/sprint training programme in the post-activation potentiation of sprint performance before, between and after resistance training sets. Twenty-six junior basketball players were randomly divided into a control and a combined training group. The combined training group performed a combined training programme consisting of 5 sets at 5-8 RM (Repetition Maximum) half-squats with sprints performed between each set. Post-activation potentiation was considered as the increase in sprint velocity in trials executed between and after the resistance sets compared with the sprint trial performed before the resistance sets of the respective first and last training session. For sprint evaluation the running distances 0-10 and 0-30 m were selected. The intervention increased both strength and sprint performance. No post-activation potentiation effect was observed during the first training session in either group. Post-activation potentiation appeared in the combined training group during the last training session of the intervention in both 0-10 and 0-30 m sprint. This study illustrates that post-activation potentiation effect on sprint performance in junior basketball players, who did not previously follow systematic resistance training, emerges after a 10-week resistance/sprint combined training programme.